Savor : a chef's hunger for more - Ali, Fatima, -2019 (Ballantine Books, an imprint of Random House, a division of Penguin Random House LLC, 2022)
"An aspiring young chef explores food and adventure, illness and mortality, coming of age and coming out in an inspiring memoir and family story that sweeps from Pakistan to New York City and beyond. Fatima Ali won the hearts of viewers as the season fifteen "Fan Favorite" of Bravo's Top Chef. After the taping wrapped and before the shows aired, Fati was diagnosed with a rare form of bone cancer, which eventually became terminal. Not one to ever slow down or admit defeat, she vowed to spend her final year traveling the world, eating delicious food, and making memories with her loved ones. But when her condition abruptly worsened, her plans were sidelined. She pivoted, determined to make her final days count as she worked to tell the story of a queer brown girl chef who set out to make a name for herself, her food, and her culture. The result is this stunning and lyrical ode to the food, family, and countries Fatima loved so much. Written both during Fati's last weeks and posthumously, this deftly woven memoir integrates the perspectives of Fatima at its core, with supporting chapters from her mother Farazeh's perspective. Flashing between past and present, readers will be transported back to Fatima's childhood, unfurling alongside that of her mother, as both were deeply affected by the cultural barriers they faced, shaping the course of their lives. At the same time, food plays an important role throughout, from the rustic stalls of the outdoor markets of Lahore to the kitchen and dining room of Meadowood, the acclaimed 3-Michelin-Star restaurant where Fatima apprenticed. Fati reflects on her life and her identity--as a chef, a daughter, a queer woman--exploring and defining her sexuality, oftentimes butting up against the more conservative and traditional views of those in her native Pakistan. This triumphant memoir is at once an exploration into the sense of wonder that made Fatima so special, and a shining testament to the resilience of the human spirit. It is, at its core, an exploration into what it means to truly live, a profound and exquisite portrait of a life that will resonate for many years to come"--